1999
DOI: 10.1002/(sici)1521-379x(199901)51:1<5::aid-star5>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Property of Huaishan (Rhizoma Dioscorea) and Matai (Eleocharis dulcis) Starches

Abstract: the starch into amylose and amylopectin, may still contain amylose and amylopectin. IntCom of Matai starch has an intermediate nature between amylose and amylopectin. It is concluded that the amylopectin molecules of Huaishan starch contain a larger amount of longer branched chains and those of Matai starch contain a larger amount of shorter branched chains. Amylograms of Matai and Huaishan starches suggest that the gelatinized starches are difficult to retrograde. Digestibility of Huaishan starch by an α-amyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
3
5
0
Order By: Relevance
“…The particle size of tapioca and maize starch is consistent with Sangeetha and Rai' s results [11]. Yu et al [3] showed that mean particle diameters of Matai starch granules was 1265 mm. The CWCS granule size observed in this study was smaller than reported results, which might be due to different cultivars and isolation methods.…”
Section: Characterization Of Cwcs Granulessupporting
confidence: 85%
See 1 more Smart Citation
“…The particle size of tapioca and maize starch is consistent with Sangeetha and Rai' s results [11]. Yu et al [3] showed that mean particle diameters of Matai starch granules was 1265 mm. The CWCS granule size observed in this study was smaller than reported results, which might be due to different cultivars and isolation methods.…”
Section: Characterization Of Cwcs Granulessupporting
confidence: 85%
“…Native starch granules can occur in three different crystalline structures, referred to as the A, B, and C type pattern according to X-ray diffractometry, and vary in their crystallinity from 15 to 45% [12]. viously reported [3]. The relative crystallinity of maize starch, CWCS and tapioca starch is 30.2%, 25.6% and 20.9%, respectively.…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…Similar results have been observed in many other studies (e.g. [148,157,210,212,242], with the initially quick degradation rate in almost every case following an asymptotic curve approaching 100% decomposition [135:38;179]. As enzyme activity is stimulated by the presence of suitable substrate, then the rates displayed in these experiments could well be approached in specific localities within soils.…”
Section: Enzymatic Degradation Of Starchmentioning
confidence: 99%
“…is a local plant in many countries, i.e., Nigeria, Jamaica, Brazil, China, and Thailand (12)(13)(14)(15). The nutrient content of yam tuber has been reported (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…The yam flour has been used in bread products and snacks (12). In addition to being used as food, it is believed that the mixture of yam flour, rice flour, and some nutrients is beneficial to infant health (15). In traditional Chinese medicine, yam (Dioscorea opposita) tuber has been used as an important invigorant.…”
Section: Introductionmentioning
confidence: 99%